PENDIDIKAN MULTIKULTURAL DALAM KURIKULUM PAI - Ridhwan, Burhanuddin; Syamsuddin; Hanifuddin (Education, Learning, and Islamic Journal, 2020)
An educational approach with a multicultural insight can provide awareness and appreciation of cultural, ethnic, and religious diversity in forming a lifestyle of unity and togetherness in a life of peace and mutual respect, and following the diversity of our society. The focus of the problems in this study are: First: the PAI learning system in a multicultural education curriculum. The method used in this research is library research or literary study, which is a study carried out to solve a problem based on a critical and in-depth study of relevant library materials following the focus of the research. The results of this study, first: The PAI learning system in the multicultural education curriculum can condition students to learn to live in differences, build mutual trust, maintain mutual understanding, uphold mutual respect, open thinking, appreciation and interdependence, and conflict resolution